Genetic diversity of blue swimming crab (Portunus pelagicus Linn 1758) from Indonesian waters (Sunda and Sahul Shelf, Wallacea region): Phylogenetic approach - Andi Aliah Hidayani; Yushinta Fujaya; Dody Dharmawan Trijuno; Nita Rukminasari; Alimuddin Alimuddin (Society for Indonesian Biodiversity, 2020)
Abstract. Hidayani AA, Fujaya Y, Trijuno DD, Rukminasari N, Alimuddin A. 2020. Genetic diversity of blue swimming crab (Portunus pelagicus Linnaeus 1758) from Indonesian waters (Sunda and Sahul Shelf, Wallacea region): Phylogenetic approach. Biodiversitas 21: 2097-2102. Blue swimming crab is one of the exploited fisheries commodities in Indonesia. This condition has contributed to the decline of their genetic diversity. The information on genetic diversity assumes importance for the conservation and the cultural purposes of species. The study aimed to determine the genetic diversity of blue swimming crabs from Indonesian waters using phylogenetic analysis. We conducted sampling of crab from several Indonesian waters, such the Aceh and Semarang (representing Sunda Shelf), Barru, South Sulawesi, and Maumere, Flores (representing Wallacea region) and Sorong, Raja Ampat and Kaimana (representing Sahul Shelf). Genetic diversity in this study using mitochondrial DNA (mtDNA) by implementing the method of Cytochrome c Oxidase Subunit I (COI). According to the findings, the blue swimming crabs from our study sites had a high genetic diversity variation. Three groups of crabs were determined using phylogenetic tree which formed three different unique clades. There was the same haplotype of crab observed from different locations, barring a sample from the Sahul Shelf which has a unique haplotype. There was no genetic speciation of crab samples from the Sunda Shelf and the Wallacea region were observed, except samples from the Sahul Shelf. Hybridization might occur between species of the crabs due to the finding of a cryptic species.